Pterostilbene improves glycaemic control in rats fed an obesogenic diet: involvement of skeletal muscle and liver. Issue 6 (10th June 2015) - Gómez-Zorita, S.; Fernández-Quintela, A.; Aguirre, L.; Macarulla, M. T.; Rimando, A. M.; Portillo, M. P.
<x xml:space="preserve">Abstract</x> This study aims to determine whether pterostilbene improved glycaemic control in rats showing insulin resistance induced by an obesogenic diet.